Pengembangan Media Pembelajaran Scrapbook dalam Materi Menulis Teks Prosedur pada Peserta Didik Kelas XI SMK Negeri 1 Kersana - Tutut Rahayu; Ghufroni Ghufroni; Prasetyo Yuli Kurniawan (Peneliti.net, 2022)
This study aims to develop scrapbook learning media in writing procedure text materials for students. class XI SMK Negeri 1 Kersana. The type of research conducted is the type of research and development (R&D). The stages carried out to examine the type of Research and Development (R&D) research include 1) potential and problems, 2) data collection, 3) product design, 4) design validation, and 5) design revision. The samples of this study were students of class XI Welding Engineering (Welding), XI Light Vehicle Engineering (TKR), and XI Multimedia. The total number of students sampled by the researcher was 87 students. Data collection techniques in this study include; observation, interview, questionnaire (questionnaire), and documentation. The results of the validation of this study, namely the aspect of content which consists of seven components is appropriate. This is evidenced by the acquisition of the total score obtained, namely 87.21, the presentation feasibility aspect consisting of three components is appropriate. This is evidenced by the total score obtained, namely 91.25, the linguistic aspect consisting of two components is appropriate. This is evidenced by the acquisition of the total value obtained, which is 93.5, the graphic aspect which consists of five components is appropriate. This is evidenced by the total score obtained is 89, that the total score for Scrapbook learning media for procedural text writing skills in class XI students of SMK Negeri 1 Kersana is 360.96. Thus, this learning media is declared suitable for use with revision.